Raum und Interieurs in Thomas Manns Erzählwerk. Materielle Kultur zwischen 'Welthäusern' und 'Urdingen' - Reidy, Julian (Hermaea. Neue Folge, 2018)
The 19th century was, in Walter Benjamin's diagnosis, "addicted to dwelling." That era's sense of space - what August Schmarsow called its Raumgefühl - shaped the narratives of Thomas Mann. This study examines Mann's literary concepts of space and interprets them less in terms of particular texts than as descriptions of material culture. It also explores the discourse, history, and ideology behind those concepts.